Assessment of polyphenols in purple and red rice bran: Phenolic profiles, antioxidant activities, and mechanism of inhibition against amylolytic enzymes - Sandra Kusumawardani; Naphatrapi Luangsakul (My University, 2024)
Pigmented Thai rice varieties, including purple (Riceberry) and red (Hommali), are gaining popularity due to their health benefits as a source of polyphenols that may exert a hypoglycemic effect through specific inhibition of amylolytic enzymes. This study determined the free phenolic extract from purple rice bran (PFE) to exhibit notably greater content of phytochemical compounds than did phenolic extracts from red rice bran, whether free (RFE) or bound fractions. This phytochemical content correlated with increased antioxidant activity and strong inhibition capacity against amylolytic enzymes, suppressing the conversion of carbohydrates into glucose. Several polyphenol compounds were identified in pigmented rice bran extracts, including benzoic acid, chlorogenic acid, ferulic acid, apigenin, and rutin; among these, flavonoids exhibited greater effect on inhibition capacity. Mechanistically, PFE was found to act as a competitive and uncompetitive inhibitor of α-amylase and α-glucosidase respectively, while RFE showed respective uncompetitive and competitive inhibitory modes.
Keywords: Phytochemical; Chlorogenic Acid; Uncompetitive inhibitor; Natural Antidiabetic Agents Studies